Análisis de la situación financiera en relación a la rentabilidad de Pharmachala Cia. Ltda. periodo 2020-2021. - Pulla Saritama, Erick Ramiro; Ajila Vacacela, Lisseth Alejandra (Machala : Universidad Técnica de Machala, 2022)
The study subject requires a financial analysis due to the present deficiency in his financial situation in relation to the profitability of the company in which it allows the entity to make timely financial decisions based on the direction of his company to maximize its profitability according to This need is created due to its deficient inventory control, which therefore presents an inadequate inventory rotation, as well as a deficiency in the accounting of sales, which would generate problems with the tax part and an erroneous indicator of profitability. Given this, an analysis of the financial situation of PHARMACHALA CIA is presented. LTDA. Period 2021 - 2021 in which it allows to study the cases of financial indicators and detect which aspects are those that must be improved for their better direction. The objective of this research work is to analyze the financial situation in relation to the profitability of PHARMACHALA Cia. Ltda., in the 2020-2021 period, for this it is necessary to analyze the financial statements of the entity, for this purpose the financial indicators or ratios will be used, establishing their influence on the profitability of the entity, in addition it seeks to analyze the management of inventories, through internal control, determining its impact on the entity's profitability indexes. For the foregoing, in the methodological context, the application of the quantitative approach with an exploratory and descriptive perspective is available, in addition, relevant data related to the problem posed will be collected through the inductive-deductive method, establishing as a focus of research what refers to the subject. study, for this, with regard to financial information, the financial statements reported to the Superintendency of Companies during the aforementioned periods will be obtained. At the same time, the determination of the sample will be non-probabilistic, of a voluntary type, in addition, methodological instruments such as interviews, surveys and observation guides will be used to identify and know the perspective of the object of study.
El sujeto de estudio requiere un análisis financiero por la presente deficiencia en su situación financiera en relación a la rentabilidad de la empresa en la cual permite a la entidad a tomar decisiones financieras oportunas en base al direccionamiento de su empresa para la maximización de su rentabilidad conforme a esta necesidad se crea debido a su deficiente control de inventarios que presenta por ende una inadecuada rotación de inventarios, además deficiencia en la contabilización de las ventas lo que generaría problemas con el la parte tributaria y un errado indicador de rentabilidad. Ante esto se presenta un análisis a la situación financiera de PHARMACHALA CIA. LTDA. Periodo 2021 – 2021 en la que permita estudiar los casos de indicadores financieros y detectar que aspectos son los que deben mejorarse para su mejor direccionamiento. El presente trabajo de investigación tiene como objetivo, analizar la situación financiera en relación a la rentabilidad de PHARMACHALA Cía. Ltda., en el periodo 2020-2021 para ello es necesario analizar los estados financieros de la entidad, para ello se hará uso de los indicadores o ratios financieros, estableciendo su influencia en la rentabilidad de la misma, además se busca analizar la gestión de inventarios., a través de un control interno, determinando su incidencia en los índices de rentabilidad de la entidad. Por lo que antecede, en el contexto metodológico se dispone de la aplicación del enfoque cuantitativo con perspectiva exploratoria y descriptiva, además se recopilará a través del método inductivo-deductivo datos relevantes relacionados con la problemática planteada, estableciendo como foco de investigación lo referente al sujeto de estudio, para ello, en lo que concierne a la información financiera se obtendrán los estados financieros reportados a la Superintendencia de Compañías durante los periodos mencionados. Paralelamente, la determinación de la muestra será no probabilístico, de tipo voluntario, además, se utilizarán instrumentos metodológicos como entrevistas, encuestas y guías de observación para identificar y conocer la perspectiva del objeto de estudio.
Keywords: ESTADOS FINANCIEROS; INDICADORES FINANCIEROS; RENTABILIDAD; ANALISIS FINANCIERO